Influence of Christian values on the quality of communication between parents and children in the socio-religious perspective. - Dawid Wiech (Rozprawy Społeczne)
Abstract The aim of the article is to analyze the influence of Christian values on the quality of communication between parents and children, with particular emphasis on the socio-religious aspect. The article discusses the social consequences of the effects of lack of orderly ties between parents and children, which are visible in: misunderstanding of themselves and the world by adolescent children, their inability to find their own place in the world and in life roles associated with it, as well as in deficiency in their autonomy in the sphere of the psyche. Then, the religious aspects of the bond between parents and children were discussed, with reference to the...- dalszy ciąg jest w pliku.